Transfer factor in prevention of Burkitt's lymphoma relapses. - Nkrumah, F.K.; Pizza, G.; Neequaye, J.; Viza, D.; De Vinci, C.; Levine, P.H. (Journal of Experimental Pathology, 1987)
Twenty-two African children with endemic Burkitt's lymphoma entered a study to evaluate the possible efficacy of a transfer factor (TF) with specific activity against Eptein-Barr virus in preventing disease relapses. Five of eleven patients have so far relapsed in the non TF-treated group as against two of eleven in the TF-treated group. The patterns of relapse and observable increased disease free remission duration in the TF-treated group strongly suggest a beneficial effect particularly in the prevention of late relapses. A larger series of patients treated with this specific TF are needed to confirm these observations in endemic Burkitt's lymphoma.